Determination of Changes in Soil Organic Carbon and Total Nitrogen Stocks under Different Stand Age of Kazdağı Fir (Abies nordmanniana subsp. equi-trojani (Steven) Spach) - SAVACI, Gamze; SARIYILDIZ, Temel (Bartin Orman Fakultesi Dergisi, 2020)
Most of the carbon in forest ecosystems is stored in the forest litter and in the soil. Soil organic carbon (SOC) and total nitrogen (TN) stocks are, however, highly variable. Forest carbon stocks and fluxes vary with forest age, and relationships with forest age are often used to estimate fluxes for regional or national carbon inventories. Therefore, it is extremely important to determine the effect of stand age on SOC and TN stocks and the amount of tree species on the distribution. The objective of this study was to estimate SOC and TN stocks of Kazdağı fir (A. nordmanniana subsp. equi-trojani (Steven) Spach) in the northwest (Ilgaz) and northeast (Inebolu) of Kastamonu. Three sites of fir stand, aged 38, 57, 60, 66, 90, 100, 183, 250, 283 and 306 years were selected in pure fir forests. The results showed significant differences in the amounts of forest litter, SOC and TN stocks among the different stand ages. Kazdağı fir stands older than 100 years had much higher forest litter than the younger fir stands. The highest amount of forest litter was under the 306 years old fir stands (30.3 Mg ha-1) while the lowest amount of forest litter was under the 100 years old fir stands (3.95 Mg ha-1). When 0-30 cm soil depth was considered, the fir stands aged 100 and over generally showed higher SOC stocks than the fir stands younger than 100 years old, with the exception of 38 and 57 years old fir stands which had the highest SOC (166.7 Mg C ha-1). Similarly, for TN stocks, it was also seen that the fir stands aged 100 or over had higher TN stocks than the fir stands younger than 100 years old. Our results have indicated that the forest litter, SOC and TN stocks of fir stands are more dependent on stand age. Our results have indicated that the forest litter, SOC and TN stocks of fir stands are more dependent on stand age.
Keywords: Carbon and nitrogen sequestration; natural forest; stand age; soil depth; Kastamonu; Orman Endüstri Mühendisliği; Forest Industry Engineering; Karbon ve azot depolaması; doğal orman; meşcere yaşı; toprak derinliği; Kastamonu; 2. Zero hunger; 15. Life on land; 13. Climate action